2022
DOI: 10.1155/2022/7640227
|View full text |Cite
|
Sign up to set email alerts
|

Mercury Exposure and Risk of Type 2 Diabetes: A Systematic Review and Meta-Analysis

Abstract: Background and Aim. Previous studies have indicated that exposure to mercury (Hg) may be associated with odds of type 2 diabetes mellitus (T2DM). However, the available evidence is contradictory. This meta-analysis aimed to examine the relationship of Hg with the risk of T2DM. Methods. Scopus and PubMed databases were systematically searched from their inception to November 2021 to obtain pertinent studies. Standardized mean differences (SMDs) with corresponding 95% confidence intervals (CIs) were calculated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 56 publications
(117 reference statements)
0
2
0
Order By: Relevance
“…A study published in Environmental Health Perspectives found that prenatal exposure to PCBs was associated with lower IQ scores in school-aged children [ 137 ]. Moreover, some research has suggested that exposure to mercury from contaminated fish may increase the risk for autoimmune disorders such as diabetes mellitus in children [ 138 ].…”
Section: Health Risks Of Fish Consumptionmentioning
confidence: 99%
“…A study published in Environmental Health Perspectives found that prenatal exposure to PCBs was associated with lower IQ scores in school-aged children [ 137 ]. Moreover, some research has suggested that exposure to mercury from contaminated fish may increase the risk for autoimmune disorders such as diabetes mellitus in children [ 138 ].…”
Section: Health Risks Of Fish Consumptionmentioning
confidence: 99%
“…It is well known that the exposure to different substances present in the environment can affect the ability of the human body to maintain glucose homeostasis, thus possibly contributing to the onset of diabetes or to the worsening of the metabolic condition in people already suffering from the disease. In recent years, several review and meta-analysis studies have summarized the scientific knowledge on the issue, focusing specifically on the effect of several environmental factors and compounds in the most common types of diabetes, i.e., type 1 diabetes [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ], type 2 diabetes [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ], and gestational diabetes [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. In addition, several studies went into more detail about the relationships between environment and diabetes, focusing on specific etiological factors of diabetes.…”
Section: Introductionmentioning
confidence: 99%